The Effect of Health Education as a Preventive Effort Against Diabetes Mellitus in Adolescents at SMA Negeri 4 Kota Parepare - Rosyida, Ishma; Sulfikar, Andi; Nurhikmah; Sri Resky Mustafa (CV. Paperhome Indonesia, 2025)
Background: Diabetes Mellitus (DM) is a major global health issue with increasing prevalence among adolescents. Health education plays a critical role in raising awareness and knowledge about the risk factors of DM and prevention strategies. This study aimed to evaluate the impact of health education on enhancing knowledge and awareness of diabetes mellitus prevention among adolescents at SMA Negeri 4 Kota Parepare. Method: A quasi-experimental study with a one-group pretest-posttest design was conducted with 29 high school students. The intervention consisted of health education sessions using audiovisual media and leaflets. Pretest and posttest assessments were performed using a structured questionnaire to measure changes in knowledge levels. Data were analyzed using paired sample t-tests. Result: Results showed a significant increase in knowledge, with the pretest mean score being 77.93 and the posttest mean score rising to 91.38 (p < 0.001). The analysis confirmed a significant difference between pretest and posttest scores, demonstrating the effectiveness of health education in improving students' knowledge of DM prevention. Conclusion: Health education using audiovisual and leaflet media significantly improves students' knowledge about DM prevention, and integrating structured health education into the school curriculum is recommended to enhance adolescent health literacy.